Assessment of market power in digital markets: Conceptual framework and empirical strategy - Tiago Sousa Prado (International Telecommunications Society (ITS), 2023)
The rise of digital platforms as a business model and a critical infrastructure for the digital economy is causing increasing trepidation among scholars and competition policy enforcers. In response to concerns about platform dominance, policies that were in place since the 1990s to keep the digital economy free from traditional regulation are being reconsidered. In these discussions, competition is considered an essential mechanism to harness the social and economic benefits of digital platforms, as it serves to attenuate potential risks to innovation, democracy, and to the media industry. This paper contributes to these discussions theoretically and empirically. It addresses some of the challenges of designing comprehensive responses to safeguard and promote competition in digital markets. The focus of the investigation is the assessment of market power in digital markets. First, a conceptual framework is developed, and it is shown that there is a need for new tests in addition to the traditional evaluation of the competitive structure of platform markets. The analysis concludes that to have significant impact in promoting competition in digital markets policy remedies should be enforced jointly on both the user- and supplier sides of the platforms. Second, the article reports results of an online survey experiment with 550 participants. The results suggest that an analysis of user responses to digital ads and data collection procedures would greatly improve the assessments of market power. Overall, this paper develops theoretically and empirically grounded contributions that will help policymakers and regulatory agencies in the design of workable approaches to assess market power in digital markets.
Keywords: 330